The role of galvanic coupling effect in determining crevice corrosion morphology - Hua, Fred Huizhong (My University, 1998)
The galvanic nature of crevice corrosion is a generally accepted concept but the coupled electrochemical behaviour and its role in crevice corrosion has not been really studied until recently. Among many arguments regarding the mechanism of crevice corrosion, whether or not being able to reasonably interpret the shape of crevice attack is an indication of whether or not the physical processes involved in crevice are profoundly understood. Based on a critical review of the state-of-the-art of the crevice corrosion studies, the necessity of studying the role of galvanic coupling effectiveness in crevice corrosion is then proposed. The concept of a uniform anode/cathodic pair with IR-drop is developed. It is shown that the galvanic coupling effect may play a significant role in crevice corrosion. For a uniform anode/cathode pair with IR-drop, the coupled potential/current relationship is a function of the kinetics on both the anode and cathode. It is found that when the anodic environmental aggressiveness exceeds certain value, the whole process is shifted from anode control to cathodic control and, therefore, the anodic dissolution rate is significantly enhanced. What complicates the process is the inevitably existing IR-drop which increases while the anodic-to-cathodic control shift occurs. This increased IR-drop is the consequence of the increase in anodic dissolution and on the other hand impedes the further increase in anodic dissolution. Therefore, the current/potential relationship in this case is being treated in a "covariant" way. In order to define the degree of the enhancement in anodic dissolution due to the coupling effect, a dimensionless parameter, the coupling coefficient η, is proposed, which is a function of anodic solution aggressiveness as well. A real corroding crevice is considered as an array of the uniform anode/cathode pair with different solution ohmic resistance. The concept of coupling effectiveness and the procedure of obtaining coupled dissolution rate as a function of solution aggressiveness and ohmic resistance of the solution phase are applied to a real corroding crevice, attempting to explain the shape of crevice attack and its evolution. Micro-electrodes techniques for measuring solution aggressiveness inside a real corroding crevice and a proper method for calculating the coupled dissolution rate at any location inside the crevice are developed. By (i) determining the local solution aggressiveness at different locations inside a corroding crevice, (ii) obtaining the kinetic information for the interior anodes in corresponding environments, and (iii) calculating the coupled dissolution rates at these locations, we are able to obtain the distribution and evolution of the coupled dissolution rate and the coupling effectiveness along the crevice. The shape of the crevice attack and its evolution with time is then attempted by integrating the coupled dissolution rate over the total time elapsed. The results show reasonably good agreement between the calculated shape of attack and its evolution and the experimental result. An alternative criterion for crevice corrosion of materials is proposed based on the response of the material to coupling effect.
Keywords: materials science; Materials Science and Engineering; Materials Science and Engineering